Purana learning model based on self-understanding to improve spiritual intelligence - Suwendra, I Wayan (Opción, 2019)
The aim of the study is to investigate Purana learning model based on self-understanding to improve spiritual intelligence. In order to study and develop this learning model, the theories used were: modern learning models, theories of self-understanding and theories of spiritual intelligence. As a result, the conceptual design of a learning model led to a prototype / hypothetical learning model, which finally being refined continously by the expert team. In conclusion, the model was considered effective due to its success in being able to improve the students’ spiritual intelligence in Purana courses based on self-understanding.